PENGARUH STRATEGI CUSTOMER BONDING TERHADAP LOYALITAS NASABAH PT. BANK SYARIAH ADAM KANTOR CABANG BENGKULU (STUDI PADA NASABAH PEMBIAYAAN MURABAHAH) - Agef Setiawan; Eti Arini (UM. Bengkulu, 2022)
This study aims to determine the effect of customer bonding strategy on customer loyalty PT. Adam Syariah Bank Bengkulu Branch Office (Study on Murabahah Financing Customers). This type of research is a quantitative approach. The population in this study is the population in this study were 67 customers of the Adam Syariah Bank Bengkulu Branch. Incidental sampling technique. A good total sampling technique is used if the total population < 100. So the number of samples from this study is 67 customers. Based on the results of research on the Influence of Customer Bonding Strategy on Customer Loyalty of PT. Adam Syariah Bank Bengkulu Branch Office (Study on Murabahah Financing Customers). The simple regression equation is Y = 2.263 + 0.540X+ e. Constant value = 2.263. positive value means that if the value of the customer bonding strategy variable remains, then customer loyalty will increase or experience an increase of 2.263. The value of the variable coefficient (X) is 0.540. Positive value is 0.540, meaning that if the customer value increases by one unit, the value (X) will increase by 0.540. The following conclusions can be drawn: There is a positive effect of customer bonding strategy (X) on customer loyalty (Y) of PT. Adam Syariah Bank Bengkulu City Branch, meaning that the higher the customer bonding strategy, the higher the customer loyalty of PT. Adam Syariah Bank Bengkulu City Branch.Keywords: Customer Bonding Strategy and Customer Loyalty